Doses e épocas de aplicação de nitrogênio: Influência na relação C/N da palhada no desenvolvimento e produtividade do milho em sistema plantio direto - Nascimento, Flávia Meinicke; Bicudo, Sílvio José [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Fernandes, Jairo Costa; Rodrigues, José Guilherme Lança; Furtado, Mariléia Barros (My University, 2012)
The objective of this research work was to evaluate the effects of doses and time of application of N on the C/N ratio of the straw cover and on the growth and productivity of maize plants growing in a no tillage system. The experiment was carried out at the Experimental Farm of the College of Agriculture of the São Paulo State University (UNESP) on its campus of Botucatu, state of São Paulo, Brazil. The treatments were distributed in the field according to a randomized complete block design in a split plot arrangement. The treatments consisted of four doses of N (0, 20, 40, and 60 kg ha-1 ) applied to oat crop and N doses (60, 80, 100, and 120 kg ha-1 ) sidedressed to corn. The development and productivity of the maize crop in a no-tillage system were found to be dependent of the C/N ratio and the straw cover. The response of the maize plants to the early application of N is dependent on doses and time of application.

Objetivou-se avaliar a influência de doses e épocas de aplicação de N e suas interferências na relação C/N da palhada no desenvolvimento e na produtividade do milho em SPD. O experimento foi conduzido em condições de campo, na FCA/UNESP, Campus de Botucatu-SP. O delineamento experimental foi de blocos ao acaso, em parcelas subdivididas, sendo consideradas parcelas as doses de nitrogênio (0; 20; 40 e 60 kg ha-1 ) aplicadas na cultura da aveia; e as doses de nitrogênio (60; 80; 100 e 120 kg ha-1 ) aplicadas em cobertura na cultura do milho, com quatro repetições. O desenvolvimento e a produtividade do milho em sistema plantio direto são dependentes da relação C/N e da palhada. A resposta da cultura do milho à aplicação antecipada de N é função das doses e das épocas destas aplicações.
Time of application and doses of N effects on the C/N ratio of the straw cover and on growth and productivity of maize plants in a no-tillage system
Keywords: Crop succession; Zea mays; Avena strigosa; Sucessão de culturas